Correlation Between Blood Pressure at Emergency Room and Mortality in Acute Non-Hemorrhagic Stroke - Azzahra, Puteri Aulia; Wahyuliati, Tri (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
According to data from the World Stroke Organization (WSO), the annual incidence of stroke is around 13.7 million new cases, with an estimated 5.5 million deaths among those impacted. Stroke caused by complications of hypertension causes 51% of the 9.4 million deaths worldwide. The neurological severity of stroke patients is associated with a decrease in systolic blood pressure of 10 mmHg for every value below 150 mmHg. The purpose of this study is to examine the correlation between blood pressure levels and mortality in acute non-hemorrhagic stroke patients. This study uses cross-sectional research methods to conduct observational research. The study included a total of 60 patients with acute non-hemorrhagic strokes who were admitted to PKU Muhammadiyah Gamping Hospital. The patients were all over the age of 50 and met the specified inclusion and exclusion criteria. Data analysis using univariate tests and Spearman's bivariate tests. The results showed that there is no significant correlation between blood pressure at hospital admission and mortality in non-hemorrhagic stroke patients, as evidenced by a p-value of 0.5. The conclusion is that there is no meaningful correlation between blood pressure on admission to the hospital and mortality in patients with acute non-hemorrhagic strokes.